Structural basis for inhibition of mycobacterial and human adenosine kinase by 7-substituted 7-(Het)aryl-7-deazaadenine ribonucleosides - Snášel, Jan; Nauš, Petr; Dostál, Jiří; Hnízda, Aleš; Fanfrlík, Jindřich; Brynda, Jiří; Bourderioux, Aurelie; Dušek, Michal; Dvořáková, Hana; Stolaříková, Jiřina; Zábranská, Helena; Pohl, Radek; et al. (Journal of medicinal chemistry, 2014)
Adenosine kinase (ADK) from Mycobacterium tuberculosis (Mtb) was selected as a target for design of antimycobacterial nucleosides. Screening of 7-(het)aryl-7-deazaadenine ribonucleosides with Mtb and human (h) ADKs and testing with wild-type and drug-resistant Mtb strains identified specific inhibitors of Mtb ADK with micromolar antimycobacterial activity and low cytotoxicity. X-ray structures of complexes of Mtb and hADKs with 7-ethynyl-7-deazaadenosine showed differences in inhibitor interactions in the adenosine binding sites. 1D (1)H STD NMR experiments revealed that these inhibitors are readily accommodated into the ATP and adenosine binding sites of Mtb ADK, whereas they bind preferentially into the adenosine site of hADK. Occupation of the Mtb ADK ATP site with inhibitors and formation of catalytically less competent semiopen conformation of MtbADK after inhibitor binding in the adenosine site explain the lack of phosphorylation of 7-substituted-7-deazaadenosines. Semiempirical quantum mechanical analysis confirmed different affinity of nucleosides for the Mtb ADK adenosine and ATP sites.
Keywords: Microbial Sensitivity Tests; ribonukleosidy; Adenine; Ribonucleosides; adenosintrifosfát; Drug Evaluation, Preclinical; Humans; preklinické hodnocení léčiv; antituberkulotika; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; adenosinkinasa; Protein Conformation; krystalografie rentgenová; mikrobiální testy citlivosti; vazebná místa; lidé; Crystallography, X-Ray; Binding Sites; Adenosine Triphosphate; adenin; Antitubercular Agents; Mycobacterium tuberculosis; Adenosine Kinase; konformace proteinů